Penerapan Economic Value Added Untuk Menilai Kinerja Keuangan - Moh Safar Ahmad; Hasanuddin Hasanuddin; Roydah Gani; Anggita Permata Yakup (Journal Of Institution And Sharia Finance, 2023)
This study aims to determine a healthy and efficient financial performance to gain profits and increase the company's performance index. This research was conducted by conducting data collection techniques using the financial ratios of PT. Asuransi Bina Dana Arta Tbk, used the ratio of Economic Value Added and measured by the formula Net Operating Profit After Tax (NOPAT), Capital Charges (CC), Weighted Average Cost of Capital (WACC), Invested Capital (IC). Obtained from the financial statements of PT Asuransi Bina Dana Arta Tbk. It can be concluded from the results of calculations that have been carried out using the measurements mentioned above that the Economic Value Added ratio measured using NOPAT is quite healthy, CC is unhealthy, WACC is quite healthy, IC is not healthy, and the EVA value is very high. unhealthy or not good enough.